Lutein Is Differentially Deposited across Brain Regions following Formula or Breast Feeding of Infant Rhesus Macaques. Issue 1 (25th January 2018) - Jeon, Sookyoung; Ranard, Katherine M; Neuringer, Martha; Johnson, Emily E; Renner, Lauren; Kuchan, Matthew J; Pereira, Suzette L; Johnson, Elizabeth J; Erdman, John W
Abstract: Background: Lutein, a yellow xanthophyll, selectively accumulates in primate retina and brain. Lutein may play a critical role in neural and retinal development, but few studies have investigated the impact of dietary source on its bioaccumulation in infants. Objective: We explored the bioaccumulation of lutein in infant rhesus macaques following breastfeeding or formula-feeding. Methods: From birth to 6 mo of age, male and female rhesus macaques ( Macaca mulatta ) were either breastfed (BF) ( n = 8), fed a formula supplemented with lutein, zeaxanthin, β-carotene, and lycopene (237, 19.0, 74.2, and 338 nmol/kg, supplemented formula-fed; SF) ( n = 8), or fed a formula with low amounts of these carotenoids (38.6, 2.3, 21.5, and 0 nmol/kg, unsupplemented formula-fed; UF) ( n = 7). The concentrations of carotenoids in serum and tissues were analyzed by HPLC. Results: At 6 mo of age, the BF group exhibited significantly higher lutein concentrations in serum, all brain regions, macular and peripheral retina, adipose tissue, liver, and other tissues compared to both formula-fed groups ( P < 0.001). Lutein concentrations were higher in the SF group than in the UF group in serum and all tissues, with the exception of macular retina. Lutein was differentially distributed across brain areas, with the highest concentrations in the occipital cortex, regardless of the diet. Zeaxanthin was present in all brain regions but only in the BF infants; it was present in both retinal regions in all groups but was significantly enhanced in BF infants compared to either formula group ( P < 0.001). β-Carotene accumulated across brain regions in all groups, but was not detected in retina. Although lycopene was found in many tissues of the SF group, it was not detected in the brain or retina. Conclusions: Although carotenoid supplementation of infant formula significantly increased serum and tissue lutein concentrations compared to unsupplemented formula, concentrations were still well below those in BF infants. Regardless of diet, occipital cortex showed selectively higher lutein deposition than other brain regions, suggesting lutein's role in visual processing in early life.